Variation in plant leaf traits affects transmission and detectability of herbivore vibrational cues. Issue 21 (30th September 2020) - Velilla, Estefania; Polajnar, Jernej; Virant‐Doberlet, Meta; Commandeur, Daniel; Simon, Ralph; Cornelissen, Johannes H. C.; Ellers, Jacintha; Halfwerk, Wouter
Abstract: Many insects use plant‐borne vibrations to obtain important information about their environment, such as where to find a mate or a prey, or when to avoid a predator. Plant species can differ in the way they vibrate, possibly affecting the reliability of information, and ultimately the decisions that are made by animals based on this information. We examined whether the production, transmission, and possible perception of plant‐borne vibrational cues is affected by variation in leaf traits. We recorded vibrations of 69 Spodoptera exigua caterpillars foraging on four plant species that differed widely in their leaf traits (cabbage, beetroot, sunflower, and corn). We carried out a transmission and an airborne noise absorption experiment to assess whether leaf traits influence amplitude and frequency characteristics, and background noise levels of vibrational chewing cues. Our results reveal that species‐specific leaf traits can influence transmission and potentially perception of herbivore‐induced chewing vibrations. Experimentally‐induced vibrations attenuated stronger on plants with thicker leaves. Amplitude and frequency characteristics of chewing vibrations measured near a chewing caterpillar were, however, not affected by leaf traits. Furthermore, we found a significant effect of leaf area, water content and leaf thickness—important plant traits against herbivory, on the vibrations induced by airborne noise. On larger leaves higher amplitude vibrations were induced, whereas on thicker leaves containing more water airborne noise induced higher peak frequencies. Our findings indicate that variation in leaf traits can be important for the transmission and possibly detection of vibrational cues. Abstract : Specific leaf traits such as leaf thickness, leaf area, and water content can influence the transmission and possibly the detectability of herbivore‐induced vibrational chewing cues. Our results are particularly interesting in light of the arms race between plants, their herbivores, and the natural enemies of plant herbivores where vibrations have been demonstrated to mediate orientation towards prey (vibrotaxis) by insect parasitoids.